Artificial Intelligence Simulation in Financial Reporting Using the GPT Platform: A Philosophical-Analytical Study on the Impact of Technology on Accounting Practices (Journal of Economic Additions, 2025)
This study analyzes the philosophical and practical impact of generative AI technologies—particularly GPT—on financial reporting. These tools enhance data analysis and accuracy, offering accountants opportunities to improve performance and minimize errors. Yet, they raise ethical and professional challenges related to transparency, accountability, bias, and the lack of regulation. Using a philosophical-analytical approach, the study examines changes in the accountant’s role within algorithm-driven environments. Findings suggest the profession must be redefined to balance efficiency with ethical standards. The study stresses the importance of human oversight and the creation of ethical legislation to govern AI use in accounting.Jel Classification Codes: M41, O33, D83
Keywords: Simulation, Artificial Intelligence , Financial Reporting , GPT Platform.